إثبات الوقف في التشريع الجزائري - الشيخ، الهمال; بحماوي، الشريف (المركز الجامعي أمين العقال الحاج موسى أق أخموك لتامنغست - معهد الحقوق والعلوم السياسية, 2023)
في ظل سياسة الدولة الجزائرية المبنية على التوجه للاستثمارات والتخلي عن ريع البترول، برز الوقف باعتباره مورد استثماري مهم وميدانا خصبا للتنافس على فعل الخير، لذلك أولته الدولة الجزائرية اهتمامها وجعلته من أولويات سياساتها التشريعية من خلال القوانين التي أصدرتها والتي تهدف إلى حماية الوقف من مختلف صور التعدي، ومن ابرز صور الحماية تنظيم وسائل إثبات الوقف طبقا لمبدأ حرية الإثبات المكرس في المادة 35 من قانون الأوقاف 91/10 والتي تنص على أنه يثبت الوقف بجميع الطرق الشرعية والقانونية. وتهدف الدراسة إلى تبيان أهم الوسائل التي اعتمدها المشرع الجزائري في إثبات الأوقاف القانونية منها والشرعية، وقد خلصت الدراسة إلى أن إخضاع الوقف للقواعد العامة في الإثبات أمر لا مناص منه مع مراعاة خصوصية البر والخير التي تميزه In light of the policy of the Algerian state based on the orientation of investments and the abandonment of oil rents, the endowment has emerged as an important investment resource and a fertile field for competition to do good, so the Algerian state has given it its attention and made it a priority of its legislative policies through the laws it issued, which aims to protect the endowment from various forms of infringement One of the most prominent forms of protection is the organization of the means of establishing endowment in accordance with the principle of freedom of proof enshrined in Article 35 of the Endowment Law 10/91, which states that the endowment is established by all legitimate and legal methods the study aims to show the most important means adopted by the Algerian legislator in proving the legal endowments, including legitimacy, and the study concluded that subjecting the endowment to the general rules of proof is unavoidable, taking into account the specificity of righteousness and goodness that distinguishes it.
Keywords: الأوقاف الإسلامية -- استثمار الأوقاف -- القوانين والتشريعات -- الجزائر